2021
DOI: 10.3389/fchem.2021.671294
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole Based Organic Semiconductor Materials for Field-Effect Transistors

Abstract: Over the past several decades, organic conjugated materials as semiconductors in organic field effect transistors (OFETs) have attracted more and more attention from the scientific community due to their intriguing properties of mechanical flexibility and solution processability. However, the device fabrication technique, design, and synthesis of novel organic semiconductor materials with high charge carrier mobility is crucial for the development of high-performance OFETs. In the past few years, more and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Research on conjugated conductive polymers has become an important aspect in OFETs owing to advantages including flexibility, easy processing, rich variety, and low cost. Further breakthroughs in the business and industry of OFETs is expected ( Zou et al, 2021 ). However, the low carrier mobility of these conjugated polymers compared to the silicon-based field-effect transistors is a major disadvantage which needs to be addressed.…”
Section: Organic Field Effect Transistormentioning
confidence: 99%
“…Research on conjugated conductive polymers has become an important aspect in OFETs owing to advantages including flexibility, easy processing, rich variety, and low cost. Further breakthroughs in the business and industry of OFETs is expected ( Zou et al, 2021 ). However, the low carrier mobility of these conjugated polymers compared to the silicon-based field-effect transistors is a major disadvantage which needs to be addressed.…”
Section: Organic Field Effect Transistormentioning
confidence: 99%
“…Diketopyrrolopyrrole (DPP), besides being a strong electron-deficient group, has several other advantages as a promising building block in the construction of dual-acceptor-type polymers. , First, the flanking groups of DPP can effectively tune the electron affinity of resultant DPP derivatives, which enables fine-tuning of charge carrier polarity of DPP-based polymers in OFETs. In our recent study, we demonstrated that, by simply varying the flanking groups of DPP-based polymers, it can achieve p-type dominant ambipolar, balanced ambipolar, or unipolar n-type carrier transport in OFETs . Second, DPP-based polymers tend to have ambipolar transport properties because the flanking groups are generally electron-donating or weak electron-accepting units. ,, Ambipolar semiconductors are more suitable candidates for the study of charge carrier polarity tunability because they allow both holes and electrons flowing in the conducting channel of OFETs under negative and positive gate voltage, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the family of D-A-D π-conjugated polymers, the diketopyrrolopyrrole (DPP) unit served as an excellent electron acceptor and attracted a great deal of attention not only for their outstanding photophysical and optoelectronic properties but also for their self-assembly properties. The molecular structure of DPP contains a planar conjugated backbone and a cyclic amide functional group, which can be substituted with a variety of alkyl chains . In addition, the substituted DPP with the appropriate donor group shows high thermal stability, fluorescent quantum yield, and exhibit enhanced charge-carrier mobility.…”
Section: Introductionmentioning
confidence: 99%